Measuring the Level of Party Institutionalization in Turkey - Mustafa Bölükbaşı (Siyasal: Journal of Political Sciences)
The main aim of this research is to combine theoretical approaches to party institutionalization with empirical operationalization. This study provides a systematic operationalization of the concept of party institutionalization using different indicators in the case of Turkish democracy. Although there has been extensive literature on the Turkish party system, there has been little discussion on party institutionalization in Turkey. The main weakness of most research is the failure to address how to quantify and measure party institutionalization. To overcome this problem, this paper offers the Party Institutionalization Index (PII). The PII is produced by the systematic operationalization of four dimensions of party institutionalization: stability, systemness, reification, and rootedness. The research shows that a political party may have significantly different scores in each dimension. This study argues that political parties with higher membership strength, geographically large-scale units, higher chronological age, more leadership changes, lower electoral volatility, and greater electoral success will become more institutionalized and survive longer. The results indicate that the CHP is the most institutionalized party in Turkey. This study also shows that political parties in Turkey, except for the HDP, display a relatively high level of institutionalization.